The Effect of Religious–Spiritual Psychotherapy on Illness Perception and Inner Strength among Patients with Breast Cancer in Iran - Davari, Safoora (Journal of religion and health, 2022)
Women diagnosed with breast cancer often suffer from illness-related issues, which negatively impact their illness perception and inner strength following diagnosis and/or during treatment. An investigation of the effectiveness of religious-spiritual psychotherapy based on the Twelver Shia Sects of Islam (RSP-TSS) was conducted among hospitalized cancer patients to determine whether it improved their disease perception and inner strength. Forty-five women (ages 31-58) diagnosed with breast cancer in Iran were randomly assigned to RSP-TSS (n = 15), attention control (n = 15) and untreated control groups (n = 15). To meet the needs of hospitalized participants, the manualized RSP-TSS protocol was adapted to consist of ten sessions, each lasting 90 min. Sessions were conducted once weekly for 10 weeks. Primary outcome measures were the Revised Illness Perception Questionnaire (IPQ-R) and the Inner Strength Questionnaire (ISQ). Data were collected in pre-intervention, post-intervention, and 4 months following the intervention. Repeated MANOVA measures showed that, as compared with the attention control and untreated control groups, the RSP-TSS group achieved significant improvements in illness perception and inner strengths, and those gains were maintained during the 4-month follow-up. By reframing illness perception and building inner strength, spiritual and religious-based interventions may improve patients coping with cancer and improve the quality of life for women hospitalized with breast cancer. These promising results warrant further investigation into the efficacy of spiritual and religious-based interventions to remediate illness perception and inner strength problems in women diagnosed with serious medical illnesses.